2017
DOI: 10.3390/met7100397
|View full text |Cite
|
Sign up to set email alerts
|

Damping Characteristics of Inherent and Intrinsic Internal Friction of Cu-Zn-Al Shape Memory Alloys

Abstract: Damping properties of the inherent and intrinsic internal friction peaks (IF PT + IF I ) of 7.5, 8.0, 8.5, and 9.0 wt. %) shape memory alloys (SMAs) were investigated by using dynamic mechanical analysis. The Cu-7.5Zn-11Al, Cu-8.0Zn-11Al, and Cu-8.5Zn-11Al SMAs with (IF PT + IF I ) β 3 (L2 1 )→γ 3 (2H) peaks exhibit higher damping capacity than the Cu-7.0Zn-11Al SMA with a (IF PT + IF I ) β 3 (L2 1 )→γ 3 (2H) peak, because the γ 3 martensite phase possesses a 2H type structure with abundant movable twin bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…3. The main or the highest intensity peak is β1'(128) martensite peak and the others are β1' martensite peaks of (122), ( 202), (0018),( 1210) and (042) according to the reference works of [37,38,42,49]. The alloy has a polycrystalline structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. The main or the highest intensity peak is β1'(128) martensite peak and the others are β1' martensite peaks of (122), ( 202), (0018),( 1210) and (042) according to the reference works of [37,38,42,49]. The alloy has a polycrystalline structure.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are many studies been done on ternary CuZnAl SMAs [5,23,[37][38][39] and some also on CuAlZn SMAs [27,40], there is no any Mg incorporated quaternary CuAlZnMg SMA work in the available literature. In this work, a CuAlZnMg SMA with a minor batch of Zn and Mg additives was produced by arc melting method.…”
mentioning
confidence: 99%
“…The β 1′ martensite appears as lath type martensite with thin plates (needle-like morphology) and γ 1′ is thicker with plate-like morphology (coarse variants) [ 5 ]. It has been reported that the γ 1′ martensite with a 2H structure in the CuZnAl alloy has abundant movable twins [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hysteresis observed in pseudoelasticity is one of the energy dissipation manifestations [ 8 ]. According to the results of Wu et al [ 10 ], in Cu-xZn-11Al (x = 7.0, 7.5, 8.0, 8.5, and 9.0 wt.%), a higher amount of martensite is transformed during martensite transformation, so the alloy exhibits a higher amount of energy dissipation due to higher hysteresis.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al investigated damping characteristics of inherent and intrinsic internal friction of Cu-Zn-Al Shape Memory Alloys[31]. The Cu-xZn-11Al SMAs are promising for practical high-damping applications under isothermal conditions because they possess good workability, low cost, acceptable mechanical properties, and the high damping capacities.Adachi et al made the phase diagram of Ni 2 MnGa 1-x Fe x on the basis of the experimental results [32].…”
mentioning
confidence: 99%